Auditory Processing after Early Left Hemisphere Injury: A Case Report - Murphy, Cristina Ferraz Borges; Stavrinos, Georgios; Chong, Kling; Sirimanna, Tony; Bamiou, Doris-Eva (Frontiers in Neurology, 2017)
Few studies have addressed the long-term outcomes of early brain injury, especially after hemorrhagic stroke. This is the first study to report a case of acquired auditory processing disorder in a 10-year-old child who had a severe left hemorrhagic cerebral infarction at 13 months of age, compromising nearly all of the left temporal lobe. This case, therefore, is an excellent and rare opportunity to investigate the presence of neural plasticity of central auditory system in a developing brain followed severe brain damage. After assuring normal functioning of the peripheral auditory system, a series of behavioral auditory processing tests was applied in dichotic and monaural listening conditions and with verbal and non-verbal stimuli. For all verbal dichotic tasks (dichotic digits, competing words, and sentences tests), good performance on the left ear, especially for Dichotic digits test (100%), and zero performance on the right ear were observed. For monaural low-redundancy tests, the patient also exhibited good performance for auditory figure-ground and time-compressed sentences tests in the left ear. In the right ear, a very poor performance was observed, but slightly better than the same in Dichotic tasks. Impaired performance was also observed in the LiSN test in terms of spatial advantage and, for the Pitch Pattern Sequence test, the only non-verbal test applied, the patient had performance within the normal range in both ears. These results are interpreted taking into consideration the anatomical location of stroke lesion and also the influence of hemispheric specialization for language on auditory processing performance.